Effective atomic number of breast tissues determined by transmission and scattering methods. (February 2020) - Gobo, Michel S.S.; Soares, L.D.H.; Poletti, M.E.
Abstract: The interaction process of the ionizing electromagnetic radiation with a composite material, formed by the combination of several atoms with different atomic number, can be described by an effective atomic number, Z eff . This parameter can be useful for characterization of tissue-equivalent and dosimetric materials, and biological tissues. In this study, the Z eff of tissue-equivalent materials (TEM) and breast tissues (normal and neoplastic) were determined by transmission (or attenuated) method which is based on the mass attenuation coefficient and by scattering (or ratio) method which is based on the Rayleigh to Compton ratio. The former provides information about the attenuation properties of the material while the latter the scattering ones. Both methods allow the determination of Z eff for materials with unknown compositions such as biological tissues. A study of sensitivity of both methods were also performed to find an optimal experimental condition to improve the detectability of smalls changes in Z eff and the method precision. Results shows that there are optimal regions to perform the measurements with each method. For both (transmission and scattering) methods, large differences were found between effective atomic numbers for adipose breast tissues and other (fibro-glandular and neoplastic) while small differences were found between fibro-glandular and neoplastic breast tissues. Additionally, among the studied TEMs, water and ethanol were found to be a good tissue-equivalents material for fibro-glandular and adipose breast tissue respectively. Highlights: Effective atomic numbers (Zeffs) were determined by transmission and scattering methods. Both methods allow the determination of Zeff of materials with unknown compositions. Sensitivity of the methods was studied to optimize the experimental conditions. Each method provides different values of Zeff for the same material. Both Zeffs are useful for choosing tissue-equivalent materials.